EXPLORING THE ROLE OF CREATIVE BEHAVIOR, ENTREPRENEURIAL SPIRIT, AND GREAT AMBITION FOR SUCCESS IN DRIVING ENTREPRENEURIAL INTENTION AMONG GEN Z AT STMB MULTI SMART MEDAN - Ang, Wisnu Stanley; Agusman; Victor (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study explores the influence of creativity, entrepreneurial spirit, and big ambition to success on the entrepreneurial desire of Generation Z students at STMB Multi Smart. Using a descriptive quantitative method, data were collected from 72 students through purposive sampling. Analysis included validity and reliability tests, classical assumption tests, and multiple linear regression. The results indicated that creativity and entrepreneurial spirit had a significant partial effect on entrepreneurial desire, whereas big ambition to success showed no significant individual effect. However, together, the three variables positively influenced entrepreneurial desire, with an R-squared value of 57.5%.